2016
DOI: 10.1159/000446389
|View full text |Cite
|
Sign up to set email alerts
|

Type-Specific Identification of Genital Human Papillomavirus Infection in Women with Cytological Abnormality

Abstract: Objectives: To estimate the frequency of human papillomavirus (HPV) infection and the genotype distribution of HPV among women with a Pap smear showing atypical squamous cells of undetermined significance (ASC-US) attending the Program for the Detection and Control of Cervical Cancer in Bogotá, Colombia. Study Design: Cervical samples from 200 women with an ASC-US Pap smear were analyzed for the presence of HPV DNA and genotype distribution using a commercial molecular technique (Linear Array®; Roche Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…22 Castellsagué et al 23 reported that HPV16, HPV18, HPV31, HPV58, and HPV52 were the top-five HR-HPV types in both normal and abnormal cervical cytology, according to estimates from 193 countries. Hernan et al 24 found that HPV16, HPV53, HPV52, HPV58, and HPV59 were the top-five genotypes in women with abnormal cervical cytology from Bogotá, Colombia. Our findings indicated that the top-five HR-HPV genotypes were HPV16, HPV58, HPV52, HPV53, and HPV51 in women with abnormal cervical cytology in Shanxi, while HPV18 was in 12th position.…”
Section: Discussionmentioning
confidence: 99%
“…22 Castellsagué et al 23 reported that HPV16, HPV18, HPV31, HPV58, and HPV52 were the top-five HR-HPV types in both normal and abnormal cervical cytology, according to estimates from 193 countries. Hernan et al 24 found that HPV16, HPV53, HPV52, HPV58, and HPV59 were the top-five genotypes in women with abnormal cervical cytology from Bogotá, Colombia. Our findings indicated that the top-five HR-HPV genotypes were HPV16, HPV58, HPV52, HPV53, and HPV51 in women with abnormal cervical cytology in Shanxi, while HPV18 was in 12th position.…”
Section: Discussionmentioning
confidence: 99%
“…X. Castellsagué et al [22] reported that HPV16, 18, 31, 58, 52 were the top five HR-HPV types in both women with normal and abnormal cervical cytology according to estimates from 193 countries. Hernan et al [23] found HPV16, 53, 52, 58 and 59 were the top five genotypes in women with abnormal cervical cytology from Bogota, Columbia. Our finding indicated that the top five HR-HPV genotypes were HPV16, 58, 52, 53 and 51 in women with abnormal cervical cytology in Shanxi Province, China, while HPV18 was in the 12th position.…”
Section: Discussionmentioning
confidence: 99%